Wybrane aspekty funkcjonowania par w Polsce i w Japonii w czasie pandemii wirusa COVID-19 - Hirayama, Maki; Pacher, Alice; Klon, Weronika; Waszyńska , Katarzyna (Studia Edukacyjne, 2021)
The COVID-19 pandemic is a global one, but the effect is different for each country and society and has different dimensions. The study investigated couple relationships during the first lockdown (also called emergency state) in Poland (N = 235) and Japan (N = 420). Based on a quantitative survey, it focuses on socio-economic issues and related concerns. The survey inquired opinions about changes in the depth of the relationships, attitude to the partner, and frequency of arguments during the lockdown. From among Polish and Japanese respondents, more than 60% declared that their current partner is the best one for the isolation. Both Japanese and Polish males seem to be more satisfied with their spouses than the female partners. The results indicate that there is a need to make more detailed cross-country comparisons in terms of the functioning of relationships during lockdown and isolation. The observations made imply that there are areas to investigate more in-depth. A follow-up survey is needed to understand whether the issues in intimate relationships will be long-term ones or whether we see them only during the pandemic. The questionnaire domains: changes in the depth of relationships, attitude to the partner and frequency of arguments during the lockdown. Method: quantitative research, survey, online questionnaire, voluntary participants collected by social media.